2010
DOI: 10.1111/j.1365-2699.2010.02443.x
|View full text |Cite
|
Sign up to set email alerts
|

Avian distribution patterns in the Guiana Shield: implications for the delimitation of Amazonian areas of endemism

Abstract: Aim To develop a methodology for defining the boundaries of the Guianan area of endemism using complementary approaches that include GIS tools, multivariate statistics and analyses of physical barriers in the distribution patterns of an entire endemic avifauna. As a case study, I used the distribution patterns of lowland terra firme forest birds.Location Guiana Shield, northern South America.Methods I identified Guianan endemics using the ornithological literature, subsequently gathering distributional data fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 75 publications
(153 reference statements)
6
48
1
7
Order By: Relevance
“…The levels of endemism we see (Figure 19) are surprisingly low compared with other known rates of endemism for the Guiana Shield (Funk et al 2007; Hollowell and Reynolds 2005; Kelloff and Funk 2004; Naka 2011). One possible explanation would simply be that cockroaches have low rates of tropical endemism.…”
Section: Discussioncontrasting
confidence: 57%
“…The levels of endemism we see (Figure 19) are surprisingly low compared with other known rates of endemism for the Guiana Shield (Funk et al 2007; Hollowell and Reynolds 2005; Kelloff and Funk 2004; Naka 2011). One possible explanation would simply be that cockroaches have low rates of tropical endemism.…”
Section: Discussioncontrasting
confidence: 57%
“…These landscapes are located in four different regions on opposite margins of the Negro and Branco rivers, and belong to distinct biogeographic units (Borges 2007, Naka 2011, Borges et al 2014: Rio Negro-Rio Branco interfluve (Arac a), eastern margin of Rio Branco (Viru a), western margin of Rio Negro (Ja u and Novo Airão), and eastern margin of Rio Negro (Uatumã). We pooled data from Novo Airão and Ja u since both belong to the same biogeographical region.…”
Section: Methodsmentioning
confidence: 99%
“…Broad scale studies may provide the greatest evidence for the forest refuge hypothesis (Adrian Quijada‐Mascareñas et al ., ; Wuster et al ., ). Both large‐scale (Naka, ) and small‐scale (Bernard & Fenton, ) studies, however, can provide evidence for the mechanisms underlying the hypothesis. We have shown that savannas may act as boundaries for dispersal in some species of blaberoid cockroaches.…”
Section: Discussionmentioning
confidence: 99%
“…The savannas of the Guianas are dispersal boundaries for some species on the large scale (Naka, ), but not necessarily on the small scale (Bernard & Fenton, ). Migrating or dispersing individuals of many animals in the Rupununi region may use the narrow riparian corridor bordering the river.…”
Section: Introductionmentioning
confidence: 99%